Comprehensively Characterizing the Cytological Features of Saccharum spontaneum by the Development of a Complete Set of Chromosome-Specific Oligo Probes - Meng, Zhuang; Zhang, Zhiliang; Yan, Tianying; Lin, Qingfang; Wang, Yu; Huang, Weiyuan; Huang, Yongji; Li, Zhanjie; Yu, Qingyi; Wang, Jianping; Wang, Kai (Frontiers in Plant Science, 2018)
Chromosome-specific identification is a powerful technique in the study of genome structure and evolution. However, there is no reliable cytogenetic marker to unambiguously identify each of the chromosomes in sugarcane (Saccharum spp., Poaceae), which has a complex genome with a high level of ploidy and heterozygosity. In this study, we developed a set of oligonucleotide (oligo)-based probes through bioinformatic design and massive synthetization. These probes produced a clear and bright single signal in each of the chromosomes and their eight homologous chromosomes in the ancient species Saccharum spontaneum (2n = 8x = 64). Thus, they can be used as reliable markers to robustly label each of the chromosomes in S. spontaneum. We then obtained the karyotype data and established a nomenclature based on chromosomal sizes for the eight chromosomes of the octoploid S. spontaneum. In addition, we also found that the 45S and 5S rDNAs demonstrated high copy number variations among different homologous chromosomes, indicating a rapid evolution of the highly repeated sequence after polyploidization. Our fluorescence in situ hybridization (FISH) assay also demonstrated that these probes could be used as cross-species markers between or within the genera of Sorghum and Saccharum. By comparing FISH analyses, we discovered that several chromosome rearrangement events occurred in S. spontaneum, which might have contributed to the basic chromosome number reduction from 10 in sorghum to 8 in sugarcane. Consistent identification of individual chromosomes makes molecular cytogenetic study possible in sugarcane and will facilitate fine chromosomal structure and karyotype evolution of the genus Saccharum.